2017
DOI: 10.1002/adhm.201700836
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic and Responsive Growth Factor Delivery from Electrospun and Hydrogel Tissue Engineering Materials

Abstract: Tissue engineering scaffolds are designed to mimic physical, chemical, and biological features of the extracellular matrix, thereby providing a constant support that is crucial to improved regenerative medicine outcomes. Beyond mechanical and structural support, the next generation of these materials must also consider the more dynamic presentation and delivery of drugs or growth factors to guide new and regenerating tissue development. These two aspects are explored expansively separately, but they must inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 103 publications
(142 reference statements)
0
44
0
Order By: Relevance
“…In vitro, a cocktail of small molecules and proteins are supplemented into the culture media to promote neural induction and regional specification into lineage-restricted neuronal subpopulations such as midbrain dopaminergic or cortical progenitors. In vivo, numerous proteins such as neurotrophins, morphogens, chemokines and axon guidance molecules have been demonstrated to influence survival, differentiation and plasticity of new and residual stem cells (Chilton, 2006;Tayalia and Mooney, 2009;Moshayedi et al, 2016;Rodriguez et al, 2018;Bruggeman et al, 2018). However, even under optimal conditions, differentiations result in heterogeneous populations inclusive of proliferating progenitors, immature and mature neurons of the desired phenotype, as well as off-target populations.…”
Section: Utilizing Biomaterials To Deliver Trophic Support In Vitro Amentioning
confidence: 99%
“…In vitro, a cocktail of small molecules and proteins are supplemented into the culture media to promote neural induction and regional specification into lineage-restricted neuronal subpopulations such as midbrain dopaminergic or cortical progenitors. In vivo, numerous proteins such as neurotrophins, morphogens, chemokines and axon guidance molecules have been demonstrated to influence survival, differentiation and plasticity of new and residual stem cells (Chilton, 2006;Tayalia and Mooney, 2009;Moshayedi et al, 2016;Rodriguez et al, 2018;Bruggeman et al, 2018). However, even under optimal conditions, differentiations result in heterogeneous populations inclusive of proliferating progenitors, immature and mature neurons of the desired phenotype, as well as off-target populations.…”
Section: Utilizing Biomaterials To Deliver Trophic Support In Vitro Amentioning
confidence: 99%
“…The urgent task is to establish the influence of conditions of three-dimensional cultivation on the efficiency of survival, proliferation and potential for directed differentiation of multipotent stem cells of different origin. In addition to form-forming and supporting functions, matrixes can also regulate growth factors releasing during different time points providing not only cell proliferation but their direct differentiation in vivo as well [30,31]. It is shown that cell-cell interaction with extracellular basement of biomaterial and growth factors provide stem cell differentiation and tissue growth [32,33].…”
Section: а B Cmentioning
confidence: 99%
“…The latter often encompasses the inclusion of mechanical stimulation and/or biomolecules (e.g., growth factors, cytokines, etc.) for tailoring biomaterials to better recapitulate in vivo tissue microenvironments biomolecular signaling and mechanobiology . However, cells immobilization in preformed ECM‐mimetic supporting scaffolds is highly challenging, often resulting in low cell seeding density and heterogeneous spatial distribution .…”
Section: Introductionmentioning
confidence: 99%